2006
DOI: 10.1109/tia.2006.873665
|View full text |Cite
|
Sign up to set email alerts
|

Fully digital hysteresis modulation with switching-time prediction

Abstract: This paper proposes a digital hysteresis-modulation technique based on switching-time prediction. Sampling controlled variables several times within a switching period, it ensures a dynamic performance comparable to that obtainable with analog hysteresis modulation. Compared to conventional digital hysteresis modulation, it avoids frequency jitter since it predicts switching transitions. Compared to hysteresis modulation based on the detection of the zero crossing of current errors, it avoids external analog c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(54 citation statements)
references
References 13 publications
1
50
0
3
Order By: Relevance
“…This problem can be solved if analog hysteretic comparators are used but at expenses of additional hardware [16]. Other solutions can be adopted by using predictive control and the DSP timers to decide the switching time [17].…”
Section: Introductionmentioning
confidence: 99%
“…This problem can be solved if analog hysteretic comparators are used but at expenses of additional hardware [16]. Other solutions can be adopted by using predictive control and the DSP timers to decide the switching time [17].…”
Section: Introductionmentioning
confidence: 99%
“…A filter is required between a VSI and the grid, reducing harmonics of the output current and imposing a current-like performance for feedback control. A simple series inductor (first order output filter) can be used [Stefanutti (2006)], but the attenuation of high frequency components, due to switching frequency, is not very pronounced. In addition, a high voltage drop is produced and the inductor, required in the design, is very bulky [Bouchafaa (2010)].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, and with the aim of increasing robustness with a fast dynamic response, sliding mode control (SMC) is the best alternative to be used [20]. Here there is a lack of research using this technique due to the following drawbacks: a) the cross-coupling between controllers through the neutral point voltage which causes severe interferences between controllers [21] and b) the variable switching frequency of the SMC which is unwanted in most industrial applications [22]. Some authors have reported several alternatives to fix the switching frequency, being the digital hysteretic modulators the most common solution [23], [24].…”
Section: Introductionmentioning
confidence: 99%
“…This problem can be solved by using analog hysteretic comparators but at the expense of increasing the hardware [25]. Other solutions are adopted by using predictive control and DSP timers in order to decide the switching time [22]. It is worth to mention that the fixed switching frequency algorithms generally assume a decoupling between controllers, which is usually obtained by removing the neutral point voltage influence from the dynamics of the controllers.…”
Section: Introductionmentioning
confidence: 99%